RELATIONSHIP BETWEEN DIURNAL PM2.5 CONCENTRATION AND CHANGES IN THE HEIGHT OF THE INVERSION LAYER IN DKI JAKARTA (CASE STUDY: AUGUST 2023) - Nur Rohmah Salaamah, Lutfiah
Air quality in Jakarta has become a critical issue due to high concentrations of Particulate Matter 2.5 (PM2.5), which poses serious health risks. One factor influencing the distribution of PM2.5 is the atmospheric inversion layer, which can restrict the dispersion of pollutants near the surface. This study examines the relationship between diurnal surface PM2.5 concentrations and changes in inversion layer height during August 2023 in DKI Jakarta. This research utilizes hourly PM2.5 concentration data from PT Nafas Indonesia and 12-hourly radiosonde data from the Soekarno-Hatta Meteorological Station. The methods employed include calculating the Bulk Richardson Number (BRN) to determine atmospheric stability, visualizing PDF and CDF to analyze the distribution of inversion layer heights, and also using Pearson correlation and linear regression while considering time and wind speed variables to assess the relationship between these factors. The results indicate that under stable and very stable atmospheric conditions, PM2.5 concentrations near the surface increase. A weak positive correlation was found between BRN values and inversion layer height, with a stronger correlation at 07:00 WIB (Western Indonesian Time) with a value of 0.28 compared to 19:00 WIB with a value of 0.15. Additionally, higher wind speeds contribute to more effective pollutant dispersion, which reduces PM2.5 concentrations and indirectly influences inversion layer height, with weak correlations observed at both 07:00 WIB and 19:00 WIB.